Intermittent claudication and physical exercise: effectiveness of a home-based program - Tomás, Maria Teresa (2012)
Peripheral arterial disease (PAD) as a high incidence in general population and 12% to 20% of population with more than 60 years has already clinical symptoms, such as intermittent claudication (IC), pain, loss of strength and functional incapacity. There are already some studies that refer the possible positive effects of physical exercise in functional consequences of PAD. The purpose of this study was to verify the results of a home-based (HB) weekly supervised physical exercise program in patients with IC in consequence of PAD in lower limbs, and observe the medium number of diary steps walked by the subjects of our study.